BODY DISSATISFACTION PROFILE AND ATTITUDES TOWARDS EATING DISORDERS AMONG STUDENTS OF PHYSICAL EDUCATION, NUTRITION, MEDICINE, AND AESTHETICS AND COSMETICS TECHNOLOGY AT THE EVANGÉLICA UNIVERSIDADE DE GOIÁS - Brito, Lucas Pereira; Pereira, Jessica Ewllynn Teixeira; Amaral, Maria Fernanda Medeiros; Vieira, Barbara Martins; Melo, Flavia; Silva, Giovanna Nascimento de Mello e (CIPEEX, 2025)
Body dissatisfaction seems to be one of the predisposing factors for the onset of eating disorders (ED), which can result in serious deficiencies in a person's nutritional status, physical and mental health, and can be potentially fatal if not treated properly. Due to the increased prevalence of EDs and their impact on the quality of life of affected individuals, an in-depth study on the subject is necessary to establish possible correlations between their development and etiological causes. The objective of this study is to evaluate the relationship between body image dissatisfaction and attitudes toward eating disorders in university students enrolled in Physical Education, Medicine, Nutrition, and Aesthetics and Cosmetics Technology courses at the Evangelical University of Goiás. This is a descriptive, cross-sectional, analytical study with a quantitative approach. Data were collected through the application of questionnaires validated in the literature, such as the Eating Attitudes Test (EAT-26) and the Body Shape Questionnaire (BSQ), in addition to a socio-demographic questionnaire. The study was submitted to the Research Ethics Committee ( – CEP/UniEVANGÉLICA) in accordance with Resolution 466/2012 of the National Health Council (CNS), which regulates research involving human subjects. Thus, discussing intervention and prevention strategies is essential to address EDs in students. This includes early identification of warning signs, promotion of a positive body image, education on nutrition and healthy eating, reduction of stigma, and creation of a supportive environment in educational institutions.